Euthynnus affinis viscera-an alternative source for protease and lipase enzymes: Characteristic and potential application as destainer agent: Euthynnus affinis viscera as source for protease and lipase enzyme - Vivi Mardina; Tisna Harmawan; Fitriani Fitriani; ELLY SUFRIADI; Febriani Febriani; Faridah Yusof (Society for Indonesian Biodiversity, 2020)
Abstract. Mardina V, Harmawan T, Fitriani, Sufriadi E, Febriani, Yusof F. 2020. Euthynnus affinis viscera-an alternative source for protease and lipase enzymes: Characteristic and potential application as destainer agent. Biodiversitas 21: 5858-5864. This study described the characterization of protease and lipase, extracted from the viscera of Euthynnus affinis and their applications as stains removal. Enzyme increased a few folds (3.99 folds for protease and 2.45 folds for lipase) after the submission to partial purification processes by ammonium sulfate precipitation and dialysis. Molecular mass assessment by SDS-PAGE showed that the enzyme solution contains three protein bands, estimated at 70, 42, and 24 kDa for protease and 32 kDa for lipase. Zymography confirmed the presence of protease and lipase in the sample. The protease and lipase exhibited optimum activities at pH 7.0 and pH 8.0 respectively, active at temperatures from 35 to 75oC with optimal activities at 65oC for both. The enzymes were stable at alkaline pH after 90 minutes (mins) of incubation and were also stable up to 65oC, showing the remaining activities of more than 70%. Samples containing protease and lipase as de-staining agents were tested by their ability to remove blood and palm oil stains, with results proving they were effective. Overall, the study showed that crude fish visceral extract contains protease and lipase and is useful in removing household stains, and could substitute for commercial detergents.